Fabrication and characterization of graphene from solid carbon dioxide - Arifutzzaman, Akhama; Yaacob, Iskandar Idris; Hawlader, Mohammad Nurul Alam; Maleque, Md. Abdul (2015)
Graphene was fabricated by a well-known technique of ignition of magnesium (Mg) metal ribbon in solid carbon dioxide. Two dry ice slabs were used as carbon source for the production of graphene. A hemispherical cavity of about 3-4 cm diameter was carved on surfaces of both dry ice slabs. About 0.5g of Mg ribbon was burnt and immediately placed into the dry ice cavity. It was then covered up by another carved slab of dry ice. After complete combustion, mixture of black and white residues was formed. It was then recovered. 20 ml of 1 M HCl acid was added to the product mixture. Reaction of HCl with MgO and unburned Mg formed MgCl2 which was then washed away by deionized water. The isolated carbon material was separated as product. Characterization of the product was performed using optical microscopy (OM), where images showed the presence of sheet-like light gray objects. Field emission scanning electron microscopy (FESEM) and transmission electron microscope (TEM) analyses revealed the presences of graphene. The lateral length of the sheet was about 3-3.5 µm and the surface area was about 3-5.5 µm2 using images analysis software.